Risiko Penyakit Infeksi terhadap Kejadian Kekurangan Energi Kronik (KEK) pada Ibu Hamil di Puskesmas Mekar Kota Kendari - Kartini, Kartini (Health Information : Jurnal Penelitian, 2017)
Chronic energy deficiency (KEK) is a condition caused by the imbalance of nutrient intake between energy and protein, so that the nutrients needed by the body is not fulfilled. This research aims to determine the risk of infection with the incidence of KEK in pregnant women in the Mekar city center. The design of the research used is case control. The research sample is a pregnant mother in the Mekar city blooming Puskesmas, amounting to 58 pregnant women. Data collection instrument in the form of a questionnaire about KEK, infectious diseases. Data analysis using Chi-square and OR tests. The results showed the number of occurrences of KEK in the pregnant women in the city blooming Puskesmas in Kendari as many as 26 people (44.8%). The number of pregnant mothers who have infectious diseases in the Puskesmas in Mekar City of Kendari as many as 11 pregnant mothers (19.0%). There is a relationship of infectious diseases with the incidence of cakes in pregnant women at the Mekar Puskesmas in the city of Kendari (X2 = 10,847; pvalue = 0.001). Expectant mothers who have an infectious disease risk 6.171 times to experience KEK (OR = 6,171; 95% CI = 2,155-17,675).